Partially Oxidized Silicon Particles for Stable Aqueous Slurries and Practical Large-Scale Making of Si-Based Electrodes. Issue 8 (12th May 2015) - Touidjine, Amina; Morcrette, Mathieu; Courty, Matthieu; Davoisne, Carine; Lejeune, Michaël; Mariage, Nicolas; Porcher, Willy; Larcher, Dominique
Abstract : The H2 bubbles resulting from the reaction of freshly prepared Si powders with water were found to impede the large-scale preparation of aqueous-based Si/CMC (Na-Carboxy-Methyl-Cellulose)/C slurries and could consequently prevent the large-scale production of composite electrode films. To understand and possibly control this reaction, silicon particles ( Siref ) have been partially oxidized either by contact with water or by air heating at elevated temperatures. By coupling kinetics, XRD, (HR)TEM/EELS, TGA/DSC, IR and gas adsorption data, the porosity/texture/surface chemistry of the resulting silica-based coating layers were found to be highly dependent on the oxidation process, while the extent of oxidation is tuned by the time-temperature of the treatment. Although fully oxidized samples are totally inactive vs. Li, the high porosity of the water-formed silica coating contrasts with the dense air-formed one that can limit access to the Si core and can block its reactivity if too thick. Controlled and optimized air-oxidative pre-treatments can prevent the H2 evolution during the slurry preparation, hence enabling the reproducible production of high-quality electrode coatings on Cu current collectors. Such treatments do not impact the reversibility of the Si-Li electrochemical reaction, even with no capacity constraints and with or without FEC addition in commercial EC/DMC/LiPF6 electrolytes.